2015
DOI: 10.1002/aelm.201400030
|View full text |Cite
|
Sign up to set email alerts
|

Ordered and Highly Conductive Carbon Nanotube Nano‐Networks in a Semiconducting Polymer Film by Solution Processing

Abstract: Nano‐engineered nanoscale composites made from a polythiophene semiconducting polymer and single‐walled carbon nanotubes are demonstrated from solution at room temperature. This solvent method decreases bundling and produces well interconnected nanotube networks with a conductivity enhancement by more than two orders of magnitude compared to a random network, and by 4.5 times compared to a nano‐engineered composite processed at high temperature, even at low nanotube concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…The mechanism for nanotube formation is based on the aniline nucleating a stacking process, which is stabilized by π–π interactions between phenazine structures [20]. Due to the strong intermolecular interaction between polymer chains, PANI NT reveals high conductivity relative to bulk polymer films [21,22,23]. Martin et al confirmed experimentally that the conductivity for randomly distributed PANI NT depends on the nanotube size, and is six times higher than that of the macromolecular polymer [7].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for nanotube formation is based on the aniline nucleating a stacking process, which is stabilized by π–π interactions between phenazine structures [20]. Due to the strong intermolecular interaction between polymer chains, PANI NT reveals high conductivity relative to bulk polymer films [21,22,23]. Martin et al confirmed experimentally that the conductivity for randomly distributed PANI NT depends on the nanotube size, and is six times higher than that of the macromolecular polymer [7].…”
Section: Introductionmentioning
confidence: 99%